East of Eden Television Production Still - Barney Rosenzweig Productions; Mace Neufeld Productions; Viacom Productions:::Creator::::::::::::; Hayman, Lee Richard:::Contributor::::::::::::
Timothy Bottoms as Adam Trask in the 1981 'East of Eden' mini-series on ABC. Digital copy only. No hard copy.